The Role of Astrocytes in Multiple Sclerosis Progression - Correale, Jorge; Farez, Mauricio F. (Frontiers in Neurology, 2015)
Multiple sclerosis (MS) is an inflammatory disorder causing central nervous system (CNS) demyelination and axonal injury. Although its etiology remains elusive, several lines of evidence support the concept that autoimmunity plays a major role in disease pathogenesis. The course of MS is highly variable; nevertheless, the majority of patients initially present a relapsing–remitting clinical course. After 10–15 years of disease, this pattern becomes progressive in up to 50% of untreated patients, during which time clinical symptoms slowly cause constant deterioration over a period of many years. In about 15% of MS patients, however, disease progression is relentless from disease onset. Published evidence supports the concept that progressive MS reflects a poorly understood mechanism of insidious axonal degeneration and neuronal loss. Recently, the type of microglial cell and of astrocyte activation and proliferation observed has suggested contribution of resident CNS cells may play a critical role in disease progression. Astrocytes could contribute to this process through several mechanisms: (a) as part of the innate immune system, (b) as a source of cytotoxic factors, (c) inhibiting remyelination and axonal regeneration by forming a glial scar, and (d) contributing to axonal mitochondrial dysfunction. Furthermore, regulatory mechanisms mediated by astrocytes can be affected by aging. Notably, astrocytes might also limit the detrimental effects of pro-inflammatory factors, while providing support and protection for oligodendrocytes and neurons. Because of the dichotomy observed in astrocytic effects, the design of therapeutic strategies targeting astrocytes becomes a challenging endeavor. Better knowledge of molecular and functional properties of astrocytes, therefore, should promote understanding of their specific role in MS pathophysiology, and consequently lead to development of novel and more successful therapeutic approaches.